PROTOTYPE OF THE WELL WATER CONDUCTIVITY SENSOR SYSTEM BASED MICROCONTROLLER - Taufiqurahman, Taufiqurahman; Harnawan, Ade Agung; Sugriwan, Iwan (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2018)
Electrical conductivity is one of the water quality parameters. The value of conductivity is an early indication of water pollution. Standard of the water conductivity value according to WHO should be less than 400 μS/cm. The prototype of the well-water conductivity sensor system consists of the power supply, temperature sensor circuit, conductivity sensor circuit, Arduino UNO microcontroller, 16x2 I2C LCD characters and the conversion equation. Therefore, It presents the conductivity value at various temperature and conductivity at 25oC by conversion equation. Furthermore, it measured the conductivity of water within 15.24 - 1031.60 μS/cm with error 0.39 – 21.48 μS/cm and the temperature of water within 20.10 – 50.20oC with error 0.13 – 0.72oC. The test of measurement from 11 sample points in the Pesayangan Martapura and Antasan Senor East Martapura, Banjar, South Kalimantan, Indonesia showed the conductivity of the well-water at the actual temperature was at the range of 128.50 – 364.51 μS/cm and the 161.97 – 364.51 μS/cm at 25oC.